The new multidimensional time/multi-frequency transform for higher order spectral analysis - Gelman, Leonid; Petrunin, Ivan (Springer Science Business Media, 2007)
A new multidimensional time/multi-frequency higher order spectral(HOS) transform is proposed for transient signals with nonlinear polynomial variation of instantaneous frequency: the short time higher order chirp spectra (HOCS) based on the higher order chirp-Fourier transform and time-domain windowing technique. The proposed transform is compared with the classical multi-frequency HOS based on the Fourier transform. It is shown that the proposed transform is more effective for processing of transient processes in comparison with the classical transform.
Keywords: Multidimensional transform; Multi-frequency; Spectral analysis; High order spectra; Chirp-Fourier transform